EGFR signaling pathway and related-miRNAs in age-related diseases: the example of miR-221 and miR-222 - Teixeira, Ana L.; Gomes, Mónica; Medeiros, Rui (Frontiers in Genetics, 2012)
Presently, neurodegenerative diseases and cancer are the most clinically problematic age-related diseases worldwide. Although being distinct disorders, their developments share common cellular mechanisms. Oncogenesis and neurodegeneration arise from the deregulation of signaling pathways, as a consequence of the resulting imbalance in cellular homeostasis. The epidermal growth factor receptor (EGFR) belongs to an important cellular signaling pathway, which regulates proliferation, differentiation, cell cycle and migration. As transcriptional targets of EGFR, the microRNAs-221/222 (miR-221/222) are important expression regulators. Dysfunctions in their networks are associated with cellular disruptions. The transcriptional activation of these miRNAs seems to be involved in cell cycle, apoptosis, metastization and in the acquisition of resistance to therapies. The up-regulation of miR-221/222 is associated with increased expression levels of matrix metalloproteinases (MMPs) and repression of cell cycle inhibitors, which are key molecules in oncogenesis and neurodegeneration processes. The interaction loop between proliferative signaling pathways and miRNA expression could reveal new targets for controlling the molecular behavior of age-related diseases.